How Does Emotion Influence Time Perception? A Review of Evidence Linking Emotional Motivation and Time Processing - Gable, Philip A.; Wilhelm, Andrea L.; Poole, Bryan D. (Frontiers in Psychology, 2022)
Emotions have a strong influence on how we experience time passing. The body of research investigating the role of emotion on time perception has steadily increased in the past twenty years. Several affective mechanisms have been proposed to influence the passing of time. The current review focuses on how three dimensions of affect—valence, arousal, and motivation—are related to time perception. The valence-based model of time perception predicts that all positive affects hasten the perception of time and all negative affects slow the perception of time. Arousal is thought to intensify the effects of the influence of valence on time perception. In much of this past work, motivational direction has been confounded with valence, whereas motivational intensity has been confounded with arousal. Research investigating the role of motivation in time perception has found that approach-motivated positive and negative affects hasten the perception of time, but withdrawal-motivated affects slow the perception of time. Perceiving time passing quickly while experiencing approach-motivated states may provide significant advantages related to goal pursuit. In contrast, perceiving time passing slowly while experiencing withdrawal-motivated states may increase avoidance actions. Below, we review evidence supporting that approach motivation hastens the passing of time, whereas withdrawal motivation slows the passing of time. These results suggest that motivational direction, rather than affective valence and arousal, drive emotional changes in time perception.